Cultivo de amebas del género Acanthamoeba ATCC 30010 con enfoque al estudio de virus nucleocitoplasmáticos de ADN de gran tamaño - Vásquez Tituana, Adamary Carolina (2024)
The genus Acanthamoeba comprises different species of free-living amoebas, often isolated from various environmental sources such as water and soil. They are frequently used in laboratories for studying other organisms. Amoebas like Acanthamoeba Castellanii are reservoirs for viruses, known for protecting these organisms from harsh environmental conditions. They are considered excellent viral hosts, particularly for giant viruses, which can be isolated by directly inoculating A. Castellanii cultures with environmental samples. In this study, laboratory cultivation protocols were established for A. Castellanii ATCC 30010 to understand the response of these microorganisms to predation interactions with viruses. An approach for the viability of this genus in liquid (PYG) and non-nutrient solid medium using Escherichia coli ATCC 25922 as a substrate was developed and applied. For identification of giant viruses, cocultures were conducted by inoculating 100 µl of A. castellanii cells in PYG medium enriched with antibiotics and water samples from lagoons in the city of Loja, in 96- well plates. Axenic cultures of amoebas were established, verifying the trophozoite state of cells and the presence of vacuoles, achieving 90-100% cell confluence. Regarding cocultures, cytopathic effects were observed in cells infected by the presence of giant viruses in the sampled lagoons. For further studies, a molecular level examination could be conducted to determine the isolated strains, along with exploring virus-host interactions, their evolutionary reasons, and environmental implications.